Varietal dependent response of barley to soil-borne Waitea circinata infection - Oros, Gyula (Acta Agraria Debreceniensis, 2015)
The disease syndrome caused by Waitea circinata, a soil-borne pathogen introduced in the past decade into Carpathian basin, visually indistinguishable of those caused by various Rhizoctonia strains in diverse host plant. Dicotyledonaceous species in general proved to be more tolerant to this new pathogen than monotyledonaceous ones. This mesophilic fungus can seriously damage cereals. The barley varieties, similarly to other plants, exhibited highly different individual reaction to soil borne infection, Bivoy being the most while Maresi the less tolerant among the 9 tested varieties. Two groups could be separated on the base of their response to Rhizoctonia; Jubilant, Bivoy, Pasadena formed one group being moderately tolerant and Anabell, Scarlett, Rex and Omega the other group of more susceptibles. Three significant factors influence on the virulence of Rhizoctonia strains comprised 62% of total variation.